In vitro anti-cancer activities of luvunga scandens (‘Mengkurat Jakun’) on oral squamous cell carcinoma cells - Ichwan, Solachuddin Jauhari Arief; Yacob, Muhammad ‘Azmi; Mohd Ramlee, Mohamad Arif; Lestari, Widya; Taher, Muhammad (Trans Tech Publications Ltd, 2021)
Luvunga scandens (“Mengkurat Jakun”) is one of the medicinal plant that produce triterpenoid compounds. A number of studies have reported that the compounds possess antiproliferative activities against various type of cancer cells. The present study aims for anticancer potential of two triterpenoids derived from L. scandens namely flindissol (compound-1) and 3- oxotirucalla-7,24-dien-21-oic-acid (compound-2) on human oral cancer HSC-3 cells. Cytotoxic activities of the triterpenoids were assessed by MTT assay. Apoptosis activities were determined by flow cytometry and caspase 3/7 assay. The MTT assay showed that compounds-1 and -2 markedly induced cytotoxicity on HSC-3 cells with IC50 10.7 μM and 8.3 μM, respectively. Flow-cytometry analysis demonstrated that both compounds increase the percentage of apoptotic cells by 18.2 % and 16.6 % respectively. Moreover, the caspase 3/7 assay confirmed that compounds-1 and -2 markedly induced caspase 3/7 activities in HSC-3 cells. These results suggest that triterpenoids extracted from L. scandens could be a potential candidate for oral cancer treatment.